Consumer price inflation and exchange rate pass-through in Jamaica - Mc Farlane, Lavern ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Analyses the relationship between exchange rate and prices in Jamaica. Looks at how this has evolved over the past twelve years.